2008
DOI: 10.1007/s11442-008-0400-2
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation patterns and species—environment relationships in the Gurbantunggut Desert of China

Abstract: The Gurbantunggut Desert is the largest stable and semi-stable sand desert in China, yet few data exist on vegetation pattern and species-environment relationships for these diverse desert landscapes. The sand dunes of the survey area are mainly of the longitudinal form from north to south, but checkerboard-shaped and honeycomb-shaped forms are also present, with the height of 10-50 m. We measured vegetation and soil data on north-south transects and compared them with vegetation and soil data on east-west tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 12 publications
(15 reference statements)
1
22
0
Order By: Relevance
“…Sang (2009) showed that, on a small scale, the vegetation coverage in the southern Gurbantu¨nggu¨t Desert was mainly affected by soil water content. Qian et al (2008) showed that on a large scale, species richness in the southern Gurbantu¨nggu¨t Desert was probably caused by the shape of the dune. From the inter-dune to the dune crest, the coverage of trees, shrubs, and herbs was mainly affected by the salinealkaline content in the soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sang (2009) showed that, on a small scale, the vegetation coverage in the southern Gurbantu¨nggu¨t Desert was mainly affected by soil water content. Qian et al (2008) showed that on a large scale, species richness in the southern Gurbantu¨nggu¨t Desert was probably caused by the shape of the dune. From the inter-dune to the dune crest, the coverage of trees, shrubs, and herbs was mainly affected by the salinealkaline content in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial distribution of the plant community is influenced by both environmental and spatial factors (Borcard et al 1992). The relationship between the vegetation and environmental factors in the Gurbantu¨nggu¨t Desert has recently been explored in several studies: these showed that the main factors causing vegetation variation were the physical and chemical properties of soils, the type of terrain, and the underground water level (Butler et al 1986;Flowers 1975;Cantero et al 1998;Requena et al 2001;Qian et al 2007Qian et al , 2008Stavi et al 2008;Sang 2009). However, the relationship between vegetation coverage, species richness, and environmental factors has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…With coverage of less than 30%, natural vegetation is dominated by Haloxylon ammodendron and H. persicum . The elevation is from 520–550 m . The desert has fixed sand dunes.…”
Section: Methodsmentioning
confidence: 99%
“…The evidence of field survey and remote sensing indicated that BSC distribution existed distinct variations in the Gurbantunggut Desert . Moreover, the landscapes of the Desert are diverse and the landform morphology represents apparent differentiation from east to west and north to south . The differences of BSCs distribution and landscape of desert can lead to variation of environmental factors .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation